(untitled) (GYMNASIUM, 2009)
The purpose of this study was to try to grow the understanding of the meanings and motivations associated with involvement in extreme sport. Since extreme sport is a relatively recent phenomenon, not so many psychological research in this area has been carried out. The sample of participants was composed of six athletes participated in two extreme sports. We adopted qualitative research methodologies in order to access meanings and motivations associated with extreme sports. Conclusions: participants in extreme sport are searching more than thrills and excitement, it is a deliberate and self-conscious approach to the activity, making informed choices rather than simply acting out unresolved conflicts or implementing distorted cognition.